Factors interfering with the adoption of good hygiene practices in public school food services in Bahia, Brazil - Ferreira, Jeane dos Santos; Araújo, Maria da Purificação Nazaré; Botelho, Raquel Braz Assunção; Zandonadi, Renata Puppin; Nakano, Eduardo Yoshio; Raposo, António; Han, Heesup; Nader, Martín; Ariza-Montes, Antonio; Akutsu, Rita de Cássia Coelho de Almeida (Frontiers in Public Health, 2022)
This cross-sectional study aimed to identify factors that interfere with the adoption of good hygiene practices in public school food services (SFS) in Bahia, Brazil. The search was conducted in public schools in Bahia/Brazil. Data collection included (i) evaluation of the adoption of Good Practices in school food services through visual observation and registration in the checklist in Good Hygienic Practices in School Food Services; (ii) Identification of schools' foodservice physical areas and environmental comfort measures; (iii) identification of sociodemographic and occupational characteristics and assessment of attitudes and level of knowledge in food hygiene. The minimum sample of 158 schools (confidence level of 95% and an error of 5%) was stratified considering the total number of districts (areas) and the schools' number per area. The data were analyzed using the Statistical Package for Science—SPSS® in version 26.0. The categorical variables were described as frequencies and percentages, and the quantitative variables as mean and standard deviation. Chi-square, Kruskal-Wallis with Tukey's post-hoc tests were used to examine qualitative variables. Independent Student t-test and ANOVA with Tukey's post-hoc tests were used to examine quantitative variables. Categorical variables were evaluated by Pearson Chi-squared tests. The Pearson test was used to analyze the correlation between Attitude and knowledge. The classification of the sanitary status was of moderate risk in 74.8% (n = 119) of the SFS (51-75% of compliance) and 25.2% (n = 40) at high risk (26-50% compliance). The average percentage of compliance for the 159 SFS in the municipality was 50.23%, obtaining a high-risk classification (26–50% compliance). In the SFS, the absence of dry goods' storage, meat preparation area, and storage of residues in more than 98% of schools was observed. Accessing attitudes, 1.4% (n = 2) of the food handlers were classified as unsatisfactory (0 to 49% of correct answers), 8.5% (n = 12) as satisfactory with restriction (50–69% of correct answers) and 90.1% (n = 128) as satisfactory. There was no correlation between Attitude and Knowledge level (p = 0.394). Considering the knowledge level, the item with the highest and lowest number of hits were: “To avoid food contamination, I wash and disinfect my hands before preparing food” and “Contaminated food will always have some change in color, smell, or taste”. There was a significant difference in the level of knowledge considering mean wage (p = 0.000), time working in school food service (p = 0.001), weekly workday (p = 0.000), and participation in food hygiene training (p = 0.000). Therefore, factors that interfered in adopting good practices in the SFS were: inadequate physical structure, absence of areas in the SFS, and absence/low number of equipment to control the production process in the cold and hot chain. Food handlers showed satisfactory attitudes and level of knowledge. However, the physical structure of the SFS compromises the adoption of good practices. It risks the safety of the food served to students at the evaluated public schools.